Resistive wall mode physics and control challenges in JT-60SA high βN scenarios. (29th August 2019) - Pigatto, L.; Aiba, N.; Bolzonella, T.; Hayashi, N.; Honda, M.; Liu, Y.Q.; Marchiori, G.; Mastrostefano, S.; Matsunaga, G.; Takechi, M.; Villone, F.
Abstract: The superconducting tokamak JT-60SA is being built in Naka (Japan) under the Broader Approach Satellite Tokamak Programme jointly by Europe and Japan, and under the Japanese national programme. JT-60SA has an important supporting mission for the development of fusion energy. It will help in both the exploitation of ITER and in the definition of an optimized DEMO design. The focus of this work is set on high scenarios, in which kink-like instabilities (e.g. one or more resistive wall modes) are potentially unstable and possibly lead to disruptions. As a fundamental step to ensure the safe realization of high plasmas, modeling activities are being carried out for MHD stability and control. The drift-kinetic damping model in particular will be considered in the present work, with a stability study in Scenario 5-like plasmas carried out with MARS-F/K. Resistive wall mode (RWM) stability is found with this model for low plasma rotation and precession drift resonance with thermal ions. The dependence on normalized and flow profile is discussed. The challenge of active control is also addressed, taking advantage of the set of RWM control coils that JT-60SA will install. A dynamic simulator, based on the CarMa code, has been developed for feedback control modeling. A demonstration of this tool is given for one of the aforementioned plasmas. Stabilization of the most unstable RWM is achieved within basic power limits. Potential applications, results and latest development of this tool are discussed.